Subclinical hypothyroidism and risk of cerebral small vessel disease: A hospital‐based observational study. (30th June 2017) - Zhang, Xiaohao; Xie, Yi; Ding, Caixia; Xiao, Jing; Tang, Yinyan; Jiang, Xuemei; Shan, Hua; Lin, Yuankai; Zhu, Yujia; Li, Chuanyou; Hu, Dan; Ling, Zhixiang; et al.
Summary: Objective: Subclinical hypothyroidism (SCH) has been associated with atherosclerosis and increased risk of ischaemic stroke. However, whether SCH is associated with cerebral small vessel disease (cSVD) remains largely unexplored. This study aimed to investigate the relationship between SCH and total cSVD burden, a composite measurement detected with magnetic resonance imaging (MRI), in patients with minor ischaemic stroke or transient ischaemic attack (TIA). Design: This was a prospective observational cohort study conducted in a tertiary referral hospital. Methods: Subclinical hypothyroidism (SCH) was defined as with mildly or moderately increased thyroid‐stimulating hormone levels (TSH, 4.5‐10.0 mIU/L), but with normal free thyroxine levels. Brain MRI presence of silent lacunar infarcts (LIs), white matter lesions (WMLs), cerebral microbleeds (CMBs) and enlarged perivascular spaces (EPVs) were summed to a validated scales ranging from 0 to 4 to represent the load of cSVD. The associations between SCH and cSVD were analysed by logistic regression analyses. Results: Subclinical hypothyroidism (SCH) was identified in 43 of 229 (18.8%) patients with minor stroke or TIA. Compared with patients without SCH, those with SCH had higher risks of WMLs, CMBs and total cSVD burden. Adjustment of potential confounders did not change these associations. Conclusions: These findings showed that SCH might be associated with the presence of WMLs, CMBs, as well as cSVD burden in patients with minor stroke or TIA.